Determinants of green innovation: The impact of internal and external knowledge - Tobias Stucki; Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2012)
Based on a comprehensive data set comprising 13 countries, 22 industries and a period of 30 years we investigate the impact of internal and external knowledge pools of both green and other than green technologies on green patent activities. It turned out that the internal green knowledge stock is positively related to green patent activities with a considerably large marginal value. The country's green knowledge stock and the green knowledge stock of the same industry in other countries are also positively related with industries' green patent activities, although with a significantly lower marginal value. External other than green knowledge stocks are negatively related with green inventions. The considerable greater marginal value for internal green knowledge stock indicates that a free-riding position on green technology investments of other industries in the same country or the same industry in other countries does not seem to be very promising in terms of green inventions. The negative marginal effect of external other than green knowledge stocks and the positive marginal value of external green knowledge stocks indicate that country level policy measures to promote green knowledge formation would provide additional positive effects for green inventions on an industry level.
Keywords: O30; O34; Q55; 330; Innovation; knowledge; patents; environment; technological change; spillovers; Technischer Fortschritt; Öko-Produkt; Patent; Technologietransfer; OECD-Staaten